Sosialisasi Pentingnya Alat Pemadam Api Ringan sebagai Antisipasi Bahaya Kebakaran di Laboratorium Motor Listrik Jurusan Teknik Mesin Universitas Mataram - Putra, I Ketut Perdana; Wiryajati, I Ketut; Mara, I Made; Adi W, IGAK Catur; Adnyani, Ida Ayu Sri; Okariawan, IDK (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Laboratories are environments with a high risk of fire, especially in engineering laboratories, which frequently use electrical equipment, batteries, and flammable materials. Fire prevention and mitigation efforts are crucial for ensuring the safety of laboratory users. One of the mandatory facilities is a portable fire extinguisher (APAR), yet many students still do not understand how to use it and its function. This community service activity involved raising awareness about the importance of APAR in the Faculty of Engineering's Electric Vehicle Laboratory, with 15 students participating. The results of the activity showed an increase in students' understanding of the function, types, and procedures for using fire extinguishers. Prior to the socialization, only 26.7% of students understood the function of fire extinguishers, but after the socialization, this increased to 100%. Understanding of fire extinguisher procedures increased to 86.7%. This activity demonstrated that socialization and hands-on practice can improve students' awareness and skills in fire prevention